Qualitative input-output analysis and national innovation system in Slovakia. (11th April 2011) - Labaj, Martin
The aim of this paper is to identify national innovation system (NIS) in the Slovak Republic by the means of sub-system minimal flow analysis (SMFA). SMFA revealed that the core of the NIS in Slovakia is based on innovation activities in rubber and plastic industry, basic metals production, chemical industry and machinery and equipments production. It also revealed underdevelopment of Slovakia in the structure of production in relation to perspective technology fields as well as in the level of technology flows. The results could help government to support innovative entrepreneurs operating in perspective technology fields. Innovation policy based on these results could support the economic growth founded on innovation driven entrepreneurship.